Diverse Sublethal Effects of a Common Fungicide Impact the Behavior and Physiology of Honey Bees - Xufeng Zhang; Qian Cao; Feng Wang; Yinyin Du; Wen Zhao; Yuan Guo; Olav Rueppell (Insects, 2025)
Honey bees and other pollinators are key to functioning natural and managed ecosystems. However, their health is threatened by many factors, including pesticides. Spraying fungicides during flowering of fruit trees is widespread even though it directly exposes pollinators to these fungicides. Here, we report a series of experiments designed to understand how the combination of propiconazole and carbendazim, marketed in China as Chunmanchun®, affects honey bee health. With an acute oral toxicity of 23.8 μg a.i./bee over 24 h in the laboratory, we considered the acute mortality risk from normal Chunmanchun® applications as relatively low. However, our comprehensive studies revealed other diverse effects: Chunmanchun® reduced memory after classic conditioning by approximately 25% and altered the activity of protective enzymes and the composition of the honey bees’ gut microbiota. Specifically, the genus Lactobacillus was decreased by ~13%, and Bartonella and Snodgrassella were increased by ~10% and ~7.5%, respectively. The gut metabolome was also disrupted in diverse ways, possibly as a functional consequence of the microbiome changes. Thus, we demonstrated numerous sublethal effects of the combination of propiconazole and carbendazim, which adds to the growing evidence that agrochemicals and fungicides in particular can harm pollinator health in subtle ways that are not captured in simple mortality assays.